Spectral Emission Dependence of Tin‐Vacancy Centers in Diamond from Thermal Processing and Chemical Functionalization. Issue 1 (5th November 2021) - Corte, Emilio; Sachero, Selene; Ditalia Tchernij, Sviatoslav; Lühmann, Tobias; Pezzagna, Sébastien; Traina, Paolo; Degiovanni, Ivo Pietro; Moreva, Ekaterina; Olivero, Paolo; Meijer, Jan; Genovese, Marco; Forneris, Jacopo
Abstract : A systematic photoluminescence (PL) investigation of the spectral emission properties of individual optical defects fabricated in diamond upon ion implantation and annealing is reported. Three spectral lines at 620, 631, and 647 nm are identified and attributed to the SnV center due to their occurrence in the PL spectra of the very same single‐photon emitting defects. It is shown that the relative occurrence of the three spectral features can be modified by oxidizing the sample surface following thermal annealing. The relevant emission properties of each class of individual emitters, including the excited state emission lifetime and the emission intensity saturation parameters are reported. Abstract : The dependence on the oxygen termination of the substrate surface of the photoluminescence (PL) emission lines observed from individual quantum emitters fabricated in diamond upon Sn ion implantation and subsequent thermal annealing is studied. A comparison with the PL properties acquired following the sole thermal annealing is performed. A characterization opto‐physical properties of the observed classes of emitters are also reported.